Analytical Study of Operational Properties of a Plate Shock Absorber of a Sucker-Rod String. (9th January 2020) - Velychkovych, Andrii; Petryk, Ivan; Ropyak, Liubomyr
Abstract : Sucker-rod pump plant operation is accompanied by inertial and shock loads, affecting the fatigue strength of sucker rods and causing possible accidents. This work proposes the original design of a shock absorber of a sucker-rod string. The peculiarity of the proposed design is the usage of thin plate packages as a bearing elastic element of the shock absorber. This approach to the elastic element' design provides the shock absorber to be easy to manufacture and operate. Sucker-rod string protection from extra load will increase the sucker-rod pump plant efficiency in general. This study aims at developing shock absorber's design and studying its most important performance options—strength and rigidity. A mechanical and mathematical model of a shock absorber's elastic element was developed in order to specify its deformation. A package of thin plates was modelled as an equivalent solid plate with a cylindrical rigidity providing equal properties of the solid model and the plate package. This model makes possible to describe analytically the stress-strain state of the shock absorber bearing elements. The work presents the final expressions of the shock absorber's strength and rigidity assessing in a convenient form for engineering practice. The numerical approbation of the obtained analytical results was carried out as the case of a plate elastic element. The authors give recommendation on the bearing unit's design of the shock absorber.